Answer :
Answer:
Option D)
[tex]2x + 4 = 3x+(-1)[/tex]
Step-by-step explanation:
We are given the following in the question:
Let x represent Kim's age
"Bob is 4 years older than twice Kim's age"
Thus, Bob's age =
[tex](4 + 2x)\text{ years}[/tex]
"Paul is 1 year younger than 3 times Kim's age."
Thus. Paul's age is
[tex](3x-1)\text{ years}[/tex]
If Bob's age and Paul's age is equal, we can write:
[tex]2x + 4 = 3x-1[/tex]
Thus, the required expression is
Option D)
[tex]2x + 4 = 3x+(-1)[/tex]
Answer:
option D
Step-by-step explanation:
i got it right on instructions